2007
DOI: 10.1108/07363760710746166
|View full text |Cite
|
Sign up to set email alerts
|

“GROw”ing up: tweenagers' involvement in family decision making

Abstract: Practitioners in particular have noted that kids are growing older younger (KGOY)and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 24 publications
1
24
1
2
Order By: Relevance
“…Belch et al (1985) and Beatty and Talpade (1994) reported that 'teenage' children (the average age of the children in these studies is 17 years) see themselves as exerting more influence on the family decision process (for example regarding both how much to spend and where to purchase) than do their parents. It is of course possible that whilst the decision may appear to be that of the child, it is set within pre-determined boundaries established by the parents (such as the parent deciding on the model of car and the child choosing the colour) (Tinson & Nancarrow, 2007). Erduran (1999) suggests that there is a difference between making a decision and deciding on a brand.…”
Section: Familial Roles and Influencementioning
confidence: 99%
“…Belch et al (1985) and Beatty and Talpade (1994) reported that 'teenage' children (the average age of the children in these studies is 17 years) see themselves as exerting more influence on the family decision process (for example regarding both how much to spend and where to purchase) than do their parents. It is of course possible that whilst the decision may appear to be that of the child, it is set within pre-determined boundaries established by the parents (such as the parent deciding on the model of car and the child choosing the colour) (Tinson & Nancarrow, 2007). Erduran (1999) suggests that there is a difference between making a decision and deciding on a brand.…”
Section: Familial Roles and Influencementioning
confidence: 99%
“…Aspirations are political, negotiated and managed vis-à-vis other family members, reflecting broader understandings of families as active, fluid and immanent (Holdsworth, 2013). That disagreement and struggles arise over aspiration-forming is perhaps not surprising, given that Tinson and Nancarrow (2007) and others discuss how ideas are formed and decisions are increasingly made democratically within families. Family relationships can shape aspirations and, in doing so, aspirations help to shape family relationships (Holdsworth, 2013).…”
Section: The Role Of Parents In the Production Of Young People's Aspimentioning
confidence: 93%
“…Teenagers today know exactly what they want and are wise and very aware of their surroundings. They are brand loyalists and empty promises will leave the marketer empty handed (Tinson and Nancarrow, 2007). Therefore, a brand's ability to 'speak' to these teens in their language will ensure loyalty.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Lindstrom (2003), this teen generation has a greater impact on family spending than any other generation before them. Not only do they have substantial private discretionary income, but also they also exert tremendous influence on everyday family spending and long term decision-making (Tinson and Nancarrow, 2007). Marshall (2010) reports that teens are often involved in some aspect of family purchase decision making and it is thought that this involvement occurs at a younger age than in the past.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation